PEDAGOGICAL CONDITIONS OF READYNESS FORMATION STUDENTS TO CREATIVE ACTIVITY (Pedagogy of Higher and Secondary Education, 2007)
The article deals with pedagogical teims as totality, of factors in interaction and intercommunication of education, training and person developing processes. It has been theoretically substantiated and experimentally checked the totality of pedagogical terms with using of non traditional methods of training for organizing of individual і group classes with elective course “I'm a creative person ” providing the resultness of readiness of pupils to creative activity.